THE IMPACT OF INTEGRATING BUILDING INFORMATION MODELING (BIM) TECHNOLOGY AND RE-ENGINEERING PROCESS IN CONSTRUCTION PROJECTS - Karimi Rad, Amirhassan (International Journal of Engineering Technologies and Management Research, 2022)
In general, the recent findings obtained in line with current construction industry conditions confirm the idea of evaluating the design before its actual implementation. Accordingly, the design needs to be examined and reviewed from various aspects before the implementation of the design in construction projects in order to eliminate the possible obstacles, problems and errors of the system. Traditional methods and techniques included multiple reviews and double-checking of maps. This method is time consuming compared to new methods and technologies, and the percentage of errors is high. Therefore, traditional methods should be replaced by more effective methods. One of the most effective advanced technologies in the world that has been faced with a great welcome around the world is Building Information Modeling (BIM). This method has significant organizational benefits and causes a systematic change in the organization. In this paper, we will examine the status of building information modeling in construction projects and organizational maturity.